Karakteristik Area Transfer pada Bangunan Transport Hub - Dwitya, Aqila Alify; Madina, Rizki Fitria (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
The transport hub building's main function is to exchange passengers from one mode to another. The transfer area is the main area of passenger transfer activities in this building. Each transport hub building certainly has different transfer area characteristics from one another. Several factors shape the spatial characteristics of this area. The purpose of this study is to determine the spatial characteristics of the transfer area and, as a theoretical study, to see how the transfer area is an adequate passenger exchange area in case studies of transport hub buildings in the world. The method used to analyze the data is descriptive qualitative. The analysis was carried out by comparing the observed data with existing theoretical variables. The results of this research then conclude in the form of several dominant factors that make the spatial character of the transfer area in transport hub buildings in the world. From the analysis that has been done, it can be concluded that there are characteristics of space-forming elements which are dominated by transparent planes, maximize incoming natural light, have an orientation to the outside of the building, have a broad shape, are dominant and are located in the center of the building.